Developing Science Skills and Introducing Traditional Herbal Medicine to Children through Science Experiment: Making Ice Cream - Agung Hidayat; Nikmal Kevin Witjaksono; Ahmad Mufasir; Akihito Fujiwara; Akbarudin Arif; Hanif Sajid Al Amna; Rayhan Rifyal Herdiansyah; Indhika Rahma Nur Hafifah; Aprillia Dwi Setyani; Muhammad Ilham Febrian; Elmi Makrifah; Fridya Ikafitri Nurhidayati (Prospect Publishing, 2023)
This activity aims to explain how the science experiment of making herbal ice cream can be used as an engaging and enjoyable method to teach science and culture. The activity took place at SD Negeri 1 Kismoyoso, Ngemplak District, Boyolali, Central Java. It was designed to help students gain understanding of scientific concepts such as chemical reactions and changes in the state of matter, as well as introduce them to the diversity of local medicinal plants. The students at SD Negeri 1 Kismoyoso were engaged in the practical process of making ice cream using herbal ingredients, specifically ginger. They also learned about the health benefits of each herbal ingredient used in making the ice cream and its connection to the scientific concepts underlying the ice cream-making process. The results of this activity demonstrated that the science experiment of making herbal ice cream can help students develop scientific skills such as observation and experimentation. Students were able to learn about various medicinal plants and their properties, as well as how these plants can be utilized to create healthy and delicious ice cream. The science experiment of making herbal ice cream serves as an effective learning method to help students explore science and culture in a holistic manner.